2012
DOI: 10.1111/j.1747-1567.2012.00827.x
|View full text |Cite
|
Sign up to set email alerts
|

Application of Artificial Intelligent to Predict Surface Roughness

Abstract: This article proposes for predicting the surface roughness of AISI 1040 steel material using the artificial intelligent. Cutting speed, feed rate, depth of cut, and nose radius have been taken into consideration as input factors and corresponding surface roughness values (Ra, Rt) as output. A series of experiments have been carried out in accordance with a full factorial design on the CNC lathe to obtain the data used for the training and testing of an artificial neural network (ANN). The developed MATLAB TM i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 24 publications
(34 reference statements)
1
9
0
Order By: Relevance
“…The detected surface roughness values were smaller than the plaque accumulation level (0.2 µm) 31) and the high microhardness values indicated high wear resistance 32) . The obtained accuracy of surface roughness and microhardness prediction was also acceptable like the other studies [13][14][15]18) . The experimental and model prediction results demonstrated that the microhardness of denture teeth decreased during the immersion period while the surface roughness increased.…”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…The detected surface roughness values were smaller than the plaque accumulation level (0.2 µm) 31) and the high microhardness values indicated high wear resistance 32) . The obtained accuracy of surface roughness and microhardness prediction was also acceptable like the other studies [13][14][15]18) . The experimental and model prediction results demonstrated that the microhardness of denture teeth decreased during the immersion period while the surface roughness increased.…”
Section: Discussionsupporting
confidence: 81%
“…Neural networks do not require any prior knowledge about the relationships that exist between the states of the parameters. There is now extensive literature showing how neural networks may be used for classification, estimation and prediction [13][14][15][16][17][18] . However, their implementations are new for denture materials.…”
Section: Introductionmentioning
confidence: 99%
“…20 Roughness can be evaluated through different parameters, such as mean roughness (Ra), root mean square (rms), roughness (Rq), and maximum peak-to-valley roughness (Ry or Rmax). 25 Using a Surftest SJ-201P roughness tester (portable surface roughness tester), the machining quality was checked by measuring the arithmetic mean of the roughness profile, denoted as Ra. A profile measuring device is generally based on a tactile measurement principle.…”
Section: Evaluation Of the Hole Qualitymentioning
confidence: 99%
“…Among them, first of all, the product designation indicators that characterize the main functions of the product and the scope of its application, and which include classification, operational and structural indicators, are highlighted. The latter, in particular, include the dimensions (subject to their tolerances) of the product and its parts [3,4].…”
Section: Introductionmentioning
confidence: 99%